Double-walled pipes and welded joints
The double pipe structure with controlled chemical compositions and welding materials for low-alloy and high-alloy steel tubes addresses crack issues during butt welding, ensuring a stable welded joint in harsh conditions.
Patent Information
- Application Number
- JP2022561278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-13
- Filing Date
- 2021-08-06
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-08-06
AI Technical Summary
Existing double pipes made of different materials face issues with cracks during butt welding, particularly when using austenitic stainless steel or Ni-based alloys, leading to unstable welded joints.
A double pipe structure composed of low-alloy steel and high-alloy steel with controlled chemical compositions for the inner and outer tubes, along with specific welding materials, to prevent cracks by managing the content of elements like Si, P, S, and Sn, ensuring the average composition satisfies certain relational expressions.
The solution effectively prevents cracks in the weld metal, allowing for a stable and sound welded joint in harsh environments.
Smart Images

Figure 0007602147000004 
Figure 0007602147000005 
Figure 0007602147000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a double pipe and a welded joint. [Background technology]
[0002] Heater tubes in thermal power boilers, waste incineration boilers, and biomass power boilers are exposed to harsh environments on the outer surface of the tubes, such as corrosion by molten salt at high temperatures and wear by unburned materials, etc. On the other hand, the inner surface of heat exchanger tubes used in the synthesis gas cooler of a coal gasification combined cycle power plant is exposed to a high-temperature corrosive environment.
[0003] By selecting appropriate materials for the outer and inner pipes, it is possible to impart excellent corrosion resistance and wear resistance to the double-walled pipe. For this reason, various double-walled pipes combining various materials have been proposed for the above-mentioned applications, as well as for applications in energy transportation and storage devices (for example, Patent Documents 1 to 9). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 4-221034 [Patent Document 2] Japanese Patent Application Publication No. 4-329852 [Patent Document 3] Japanese Patent Application Publication No. 5-17841 [Patent Document 4] Japanese Patent Application Publication No. 6-306518 [Patent Document 5] Japanese Patent Application Publication No. 7-41911 [Patent Document 6] Japanese Patent Application Publication No. 7-90496 [Patent Document 7] Japanese Patent Application Publication No. 7-90540 [Patent Document 8] Japanese Patent Application Publication No. 8-232031 [Patent Document 9] JP 2013-159840 A Summary of the Invention [Problem to be solved by the invention]
[0005] When these double-walled pipes are used in structures such as heaters, they are assembled by butt welding. Problems and solutions to be solved when welding the individual materials that make up the outer or inner pipe of the double-walled pipe have been studied for a long time. However, the study of welding double-walled pipes made of different materials has not been sufficient.
[0006] In particular, in recent years, in order to improve the efficiency of construction, there are cases where the welding material is not switched between the inner and outer pipes during multi-layer welding, and all layers are welded using welding materials for austenitic stainless steels or Ni-based alloys. In such cases, cracks may occur in the weld metal near the fusion line near the boundary between the inner and outer pipes. Therefore, there is a strong demand for preventing such cracks. It is known that clad steel plates are similarly constructed by combining different materials, but the above problem is particularly noticeable when circumferentially welding double-walled pipes.
[0007] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a double-walled pipe that prevents cracks from occurring in the weld metal during butt welding of pipes and enables a sound welded joint to be stably obtained, and a welded joint using the same. [Means for solving the problem]
[0008] The present invention relates to the following double pipe and welded joint.
[0009] (1) A double pipe having a first pipe and a second pipe, The chemical composition of the first tube is, in mass%, C: More than 0.060% and less than 0.400% Si: 0.01 to 1.00%, Mn: 0.01 to 1.20%, P:0.0350% or less, S: 0.0150% or less, Sn: 0.0005~0.0400%, Al: 0.040% or less, N: 0.050% or less, O: 0.030% or less, The balance is Fe and impurities. The chemical composition of the second tube is, in mass%, C: 0.003 to 0.100%, Si: 0.01 to 1.50%, Mn: 0.01-2.20%, P:0.0400% or less, S: 0.0100% or less, Sn: 0.0005~0.0300%, Ni: 7.0-52.0%, Cr: 15.0-27.0%, Al: 0.001 to 0.600%, N: 0.001 to 0.150%, O: 0.030% or less, The balance is Fe and impurities. Satisfying the following formulas (i) and (ii): double tube. S ave +6×P ave +20×S ave +2×Sn ave ≦1.1000 (i) 0.0015≦4×S ave +Sn ave (ii) In the above formula, the meanings of each symbol are as follows: S ave : Average value of Si content of the first and second tubes (mass%) P ave : Average value of P content in the first and second pipes (mass%) S ave : Average value of S content in the first and second pipes (mass%) Sn ave : Average value of Sn content of the first and second tubes (mass%)
[0010] (2) The chemical composition of the first tube is, in mass%, replacing a part of Fe, Cr:9.50% or less, The total of one or more selected from Cu, Ni, and Co: 1.00% or less, Sum of Mo and / or W: 4.00% or less, The total of one or more selected from V, Nb, Ti, and Ta: 1.00% or less, B: 0.0200% or less, Total of Ca and / or Mg: 0.0100% or less, REM: 0.0500% or less, Contains one or more selected from the group consisting of The double pipe described in (1) above.
[0011] (3) The chemical composition of the second tube is, in mass%, replacing a part of Fe, Sum of Cu and / or Co: 6.00% or less; Sum of Mo and / or W: 8.00% or less, The total of one or more selected from V, Nb, Ti, and Ta: 2.00% or less, B: 0.0200% or less, Total of Ca and / or Mg: 0.0100% or less, REM: 0.0500% or less, Contains one or more selected from The double pipe according to (1) or (2) above.
[0012] (4) A welded joint comprising a double pipe according to any one of (1) to (3) above. Effect of the Invention
[0013] According to the present invention, it is possible to obtain a double-walled pipe which is capable of preventing cracks from occurring in the weld metal during butt welding of the pipes and which can stably obtain a sound welded joint. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic cross-sectional view showing the shape of a test piece subjected to groove processing in the examples. [Diagram 2]FIG. 2 is a schematic diagram showing the shape of a restraint welding test specimen. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In order to solve the above-mentioned problems, the present inventors conducted a detailed study on cracks that occur in the weld metal when a double-walled pipe made of a combination of low-alloy steel and a high-alloy steel, each containing 0.0005 to 0.0400% and 0.0005 to 0.0300% Sn, is butt-welded using a Ni-based alloy welding material, with the aim of improving corrosion resistance. As a result, the following findings were clarified.
[0016] (a) The cracks that occurred during welding occurred in the weld metal near the fusion line near the boundary between the inner and outer tubes, that is, in the area where the inner and outer tubes melt and mix in roughly equal proportions and are particularly susceptible to the influence of the components of the base material (the inner and outer tubes). The area where the cracks occurred had a structure that had solidified in a single austenite phase.
[0017] (b) The cracks were more likely to occur with increasing Si, P, S and Sn contents in the inner and outer tubes. Furthermore, the cracks occurred at the columnar grain boundaries of the weld metal close to the fusion boundary, where the concentrations of Si, P, S and Sn were confirmed.
[0018] From these results, it was believed that the cracks occurred for the following reasons.
[0019] (c) Si, P, S and Sn are distributed between the liquid phase and the solid phase (austenite phase) during the solidification of the weld metal, and are concentrated at the columnar grain boundaries where the solid phases meet. Since all of these elements lower the solidus temperature, it is believed that the liquid phase remained at the columnar grain boundaries until the end of solidification, and that the shrinkage stress during solidification caused the opening.
[0020] (d) In order to stably prevent this cracking, it was found that the average amounts of Si, P, S and Sn contained in the outer and inner tubes must be controlled to within a range that satisfies a specific relationship. The lower the amounts of these elements, the less likely cracking will occur in the weld metal.
[0021] (e) On the other hand, it was also revealed that if the contents of S and Sn among these elements are drastically reduced, poor penetration becomes more likely to occur during stack welding.
[0022] (f) S is a surface active element that strengthens the inward convection in the molten pool during welding. This makes it easier to transport heat from the arc in the depth direction, deepening the penetration depth. In addition, Sn evaporates from the molten pool surface during welding, forms a current path for the arc, and increases the current density of the arc, which also has the effect of deepening the penetration depth.
[0023] (g) Therefore, when the S and Sn contents are extremely low, the above-mentioned effects are not sufficiently obtained, and it is considered that poor penetration is likely to occur during stack welding.
[0024] (h) It was found that in order to prevent poor penetration, it is necessary to control the average values of S and Sn contents of the outer and inner tubes so as to be within a range satisfying a predetermined relationship.
[0025] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.
[0026] (A) Overall configuration A double-walled pipe has a structure in which an outer pipe and an inner pipe are metallurgically bonded, and is also called a "clad pipe." The double-walled pipe according to the present invention comprises a first pipe and a second pipe. In the present invention, depending on the application, the first pipe may be used as the outer pipe and the second pipe as the inner pipe, or the second pipe may be used as the outer pipe and the first pipe as the inner pipe.
[0027] The double-walled pipe of the present invention is a seamless steel pipe (sometimes called a "seamless steel pipe"). There are no particular limitations on the dimensions of the double-walled pipe, but it is preferable that the outer diameter is 25.4 to 114.3 mm, the thickness is 2.0 to 15.0 mm, and the ratio of the second pipe made of a high alloy steel described below to the overall thickness of the pipe is 0.10 to 0.50.
[0028] As described below, the first tube is made of a low alloy steel and the second tube is made of a high alloy steel. The chemical compositions of the first tube and the second tube are each described in detail below.
[0029] (B) Chemical composition of the first tube The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0030] C: More than 0.060% and less than 0.400% C contributes to ensuring strength at room temperature and high temperature by dissolving in the matrix or precipitating as carbide during use at high temperature. To obtain this effect, C is contained in an amount exceeding 0.060%. However, excessive C content leads to hardening of the heat-affected zone during butt welding and increases the cold cracking susceptibility. Therefore, the C content is set to 0.400% or less. The C content is preferably more than 0.100%, and more preferably 0.110% or more. The C content is preferably 0.380% or less, and more preferably 0.350% or less.
[0031] Silicon: 0.01 to 1.00% Silicon has a deoxidizing effect and is an effective element for improving corrosion resistance and oxidation resistance at high temperatures. To obtain this effect, the silicon content is set to 0.01% or more. However, if it is contained in excess, it is mixed into the weld metal during welding and increases the solidification cracking susceptibility. Therefore, the silicon content must be set to 1.00% or less and must satisfy the relationship with the contents of P, S and Sn described below. The silicon content is preferably 0.03% or more, and more preferably 0.05% or more. The silicon content is preferably 0.90% or less, and more preferably 0.80% or less.
[0032] Mn: 0.01 to 1.20% Mn, like Si, has a deoxidizing effect, and also improves hardenability and contributes to improving strength. To obtain this effect, the Mn content is set to 0.01% or more. However, excessive content of Mn leads to embrittlement during use at high temperatures. Therefore, the Mn content is set to 1.20% or less. The Mn content is preferably 0.03% or more, and more preferably 0.05% or more. Moreover, the Mn content is preferably 1.10% or less, and more preferably 1.00% or less.
[0033] P:0.0350% or less P is mixed into the weld metal during welding and increases the solidification cracking susceptibility. For this reason, the P content is set to 0.0350% or less. Furthermore, it is necessary to satisfy the relationship with the contents of Si, S, and Sn described below. The P content is preferably 0.0330% or less, and more preferably 0.0300% or less. There is no need to set a lower limit for the P content, and it may be 0 (zero), but an extreme reduction will increase the steelmaking cost. In addition, P has a not small effect of increasing strength. To obtain this effect, the P content is preferably 0.0015% or more, and more preferably 0.0030% or more.
[0034] S: 0.0150% or less Like P, S is mixed into the weld metal during welding and significantly increases the solidification cracking susceptibility. For this reason, the S content is set to 0.0150% or less. Furthermore, it is necessary to satisfy the relationship with the contents of Si, P, and Sn described below. The S content is preferably 0.0130% or less, and more preferably 0.0100% or less. There is no need to set a lower limit for the S content, and it may be 0 (zero), but if it is reduced too much, the penetration depth during welding becomes small and poor fusion is likely to occur. For this reason, the S content satisfies the relationship with Sn described below and is preferably 0.0001% or more, and more preferably 0.0002% or more.
[0035] Sn: 0.0005~0.0400% Sn has the effect of concentrating under the scale on the surface of the steel and improving corrosion resistance. It also mixes into the weld metal during welding, increasing the penetration depth and suppressing the occurrence of incomplete fusion. To obtain this effect, the Sn content must be 0.0005% or more and must satisfy the relationship with the S content described below. On the other hand, if it is contained in excess, it increases the solidification cracking susceptibility during welding. For this reason, the Sn content must be 0.0400% or less and must satisfy the relationship with the Si, P and Sn contents described below. The Sn content is preferably 0.0008% or more, and more preferably 0.0010% or more. The Sn content is preferably 0.0380% or less, and more preferably 0.0350% or less.
[0036] Al: 0.040% or less Al is contained for deoxidation. However, excessive content of Al leads to a decrease in toughness. For this reason, the Al content is set to 0.040% or less. The Al content is preferably 0.035% or less, and more preferably 0.030% or less. There is no need to set a lower limit for the Al content, and it may be 0 (zero), but if it is reduced too much, the deoxidation effect is not sufficiently obtained, the cleanliness of the steel decreases, and the manufacturing cost increases. For this reason, the Al content is preferably 0.001% or more, and more preferably 0.002% or more.
[0037] N: 0.050% or less Excessive N content leads to a decrease in toughness. For this reason, the N content is set to 0.050% or less. The N content is preferably 0.045% or less, and more preferably 0.040% or less. There is no need to set a lower limit for the N content, and it may be 0 (zero), but extreme reduction leads to an increase in steelmaking costs. In addition, N forms nitrides, which has the effect of increasing strength to some extent. To obtain this effect, the N content is preferably 0.001% or more, and more preferably 0.003% or more.
[0038] O: 0.030% or less Excessive O content leads to deterioration of workability and ductility. For this reason, the O content is set to 0.030% or less. The O content is preferably set to 0.025% or less, and more preferably set to 0.020% or less. There is no need to set a lower limit for the O content, and it may be 0 (zero), but extreme reduction leads to an increase in steelmaking costs. For this reason, the O content is preferably set to 0.001% or more, and more preferably set to 0.003% or more.
[0039] The chemical composition of the first tube is made up of the balance Fe and impurities. Note that "impurities" refer to substances that are mixed in due to various factors during the industrial production of steel materials, including raw materials such as ores and scraps.
[0040] The chemical composition of the first tube may contain one or more elements selected from the group below in place of a portion of Fe. The reasons for this will be described below.
[0041] Cr:9.50% or less The total of one or more selected from Cu, Ni and Co: 1.00% or less Total of Mo and / or W: 4.00% or less The total of one or more selected from V, Nb, Ti and Ta: 1.00% or less B: 0.0200% or less Total of Ca and / or Mg: 0.0100% or less REM: 0.0500% or less
[0042] Cr:9.50% or less Cr is effective in improving corrosion resistance and strength at high temperatures, so it may be contained as necessary. However, if contained in excess, toughness decreases, so if contained, the Cr content is set to 9.50% or less. The Cr content is preferably 9.40% or less, and more preferably 9.20% or less. If it is desired to reliably obtain the above effects, the Cr content is preferably 0.01% or more, and more preferably 0.02% or more.
[0043] The total of one or more selected from Cu, Ni and Co: 1.00% or less Cu, Ni and Co are all effective in improving hardenability and strength, and may be contained as necessary. However, since they are all expensive elements, when they are contained, the total content of one or more selected from these elements is set to 1.00% or less. The above total content is preferably 0.90% or less, and more preferably 0.80% or less. In order to reliably obtain the above effects, the above total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0044] Total of Mo and / or W: 4.00% or less Both Mo and W are dissolved in the matrix and contribute to improving high-temperature strength, so they may be contained as necessary. However, if contained in excess, coarse intermetallic compounds and / or carbides are generated during use at high temperatures, resulting in a decrease in toughness, so if contained, the total content of Mo and / or W is set to 4.00% or less. The above total content is preferably 3.80% or less, and more preferably 3.50% or less. If it is desired to reliably obtain the above effects, the above total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0045] The total of one or more selected from V, Nb, Ti and Ta: 1.00% or less V, Nb, Ti and Ta may be contained as necessary because they all form fine carbonitrides during use at high temperatures and contribute to improving high-temperature strength. However, excessive content of these elements generates a large amount of coarse carbonitrides, which leads to a decrease in toughness, so when these elements are contained, the total content of one or more selected from these elements is set to 1.00% or less. The total content is preferably 0.90% or less, and more preferably 0.80% or less. If it is desired to reliably obtain the above effects, the total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0046] B: 0.0200% or less B may be added as necessary, since it improves hardenability and contributes to improving strength. However, if it is added in excess, it is mixed into the weld metal during welding and increases solidification cracking susceptibility, so if it is added, the B content is set to 0.0200% or less. The B content is preferably 0.0180% or less, and more preferably 0.0150% or less. If it is desired to reliably obtain the above effects, the B content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0047] Total of Ca and / or Mg: 0.0100% or less Both Ca and Mg may be added as necessary to improve hot workability. However, excessive addition significantly reduces cleanliness and impairs hot workability, so when added, the total content of Ca and / or Mg is set to 0.0100% or less. The total content is preferably 0.0080% or less, and more preferably 0.0060% or less. In order to reliably obtain the above effects, the total content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0048] REM: 0.0500% or less Like Ca and Mg, REM may be added as necessary to improve hot workability. However, excessive addition significantly reduces cleanliness and impairs hot workability, so if added, the REM content is set to 0.0500% or less. The REM content is preferably 0.0400% or less, and more preferably 0.0300% or less. If it is desired to reliably obtain the above effects, the REM content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0049] "REM" is a general term for 17 elements, including Sc, Y, and lanthanides, and the REM content refers to the total content of one or more REM elements. REM is generally contained in misch metal. For this reason, for example, misch metal may be added to the alloy to make the REM content fall within the above range.
[0050] (C) Chemical composition of the second tube The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0051] C: 0.003 to 0.100% C stabilizes the austenite structure and contributes to ensuring high-temperature strength. To achieve this effect, the C content is set to 0.003% or more. However, excessive C content generates carbides during welding or use at high temperatures, resulting in a decrease in corrosion resistance. Therefore, the C content is set to 0.100% or less. The C content is preferably 0.005% or more, and more preferably 0.008% or more. Moreover, the C content is preferably 0.090% or less, and more preferably 0.080% or less.
[0052] Silicon: 0.01 to 1.50% Si has a deoxidizing effect and is an element effective in improving corrosion resistance and oxidation resistance at high temperatures. To obtain this effect, the Si content is set to 0.01% or more. However, if it is contained in excess, it is mixed into the weld metal during welding, increasing the solidification cracking sensitivity and impairing the stability of the austenitic structure, resulting in a decrease in high-temperature strength. Therefore, the Si content is set to 1.50% or less and must satisfy the relationship with P, S and Sn described below. The Si content is preferably 0.03% or more, more preferably 0.05% or more. The Si content is preferably 1.30% or less, more preferably 1.00% or less.
[0053] Mn: 0.01 to 2.20% Mn has a deoxidizing effect and increases the stability of the austenitic structure, thereby contributing to ensuring high-temperature strength. To obtain this effect, the Mn content is set to 0.01% or more. However, excessive content of Mn leads to embrittlement during use at high temperatures. Therefore, the Mn content is set to 2.20% or less. The Mn content is preferably 0.03% or more, and more preferably 0.05% or more. Moreover, the Mn content is preferably 2.00% or less, and more preferably 1.80% or less.
[0054] P:0.0400% or less P is mixed into the weld metal during welding and increases the solidification cracking susceptibility. For this reason, the P content is set to 0.0400% or less. Furthermore, it is necessary to satisfy the relationship with the contents of Si, S, and Sn described below. The P content is preferably 0.0380% or less, and more preferably 0.0350% or less. There is no need to set a lower limit for the P content, and it may be 0 (zero), but an extreme reduction will increase the steelmaking cost. In addition, P has a not small effect of increasing strength. To obtain this effect, the P content is preferably 0.0030% or more, and more preferably 0.0050% or more.
[0055] S: 0.0100% or less Like P, S is mixed into the weld metal during welding and significantly increases the solidification cracking susceptibility. It also increases the liquation cracking susceptibility of the weld-affected zone. For this reason, the S content is set to 0.0100% or less. Furthermore, it is necessary to satisfy the relationship with the contents of Si, P, and Sn described below. The S content is preferably 0.0090% or less, and more preferably 0.0080% or less. There is no need to set a lower limit for the S content, and it may be 0 (zero), but if it is reduced too much, the penetration depth during welding becomes small and poor fusion is likely to occur. For this reason, the S content satisfies the relationship with Sn described below and is preferably 0.0001% or more, and more preferably 0.0002% or more.
[0056] Sn: 0.0005~0.0300% Sn has the effect of improving corrosion resistance. In addition, it is mixed into the weld metal during welding, and increases the penetration depth to suppress the occurrence of incomplete fusion. In order to obtain this effect, the Sn content must be 0.0005% or more, and must satisfy the relationship with the S content described below. On the other hand, if it is contained excessively, it increases the solidification cracking susceptibility during welding and increases the liquation cracking susceptibility of the weld-affected zone. For this reason, the Sn content must be 0.0300% or less, and must satisfy the relationship with the Si, P and Sn contents described below. The Sn content is preferably 0.0008% or more, and more preferably 0.0010% or more. In addition, the Sn content is preferably 0.0280% or less, and more preferably 0.0250% or less.
[0057] Ni: 7.0~52.0% Ni stabilizes the austenite structure and contributes to high-temperature strength. Furthermore, it enhances corrosion resistance in an environment where chloride ions are present. To obtain this effect, the Ni content is set to 7.0% or more. However, since Ni is an expensive element, excessive inclusion of Ni leads to increased costs. Therefore, the Ni content is set to 52.0% or less. The Ni content is preferably 7.2% or more, and more preferably 7.5% or more. Moreover, the Ni content is preferably 48.0% or less, and more preferably 45.0% or less.
[0058] Cr: 15.0~27.0% Cr contributes to improving oxidation resistance and corrosion resistance at high temperatures. To achieve this effect, the Cr content is set to 15.0% or more. However, excessive content impairs the stability of the austenitic structure, resulting in a decrease in high-temperature strength. Therefore, the Cr content is set to 27.0% or less. The Cr content is preferably 15.2% or more, and more preferably 15.5% or more. Moreover, the Cr content is preferably 26.8% or less, and more preferably 26.5% or less.
[0059] Al: 0.001 to 0.600% Al is contained for deoxidation. Furthermore, during use at high temperatures, it combines with Ni and precipitates as an intermetallic compound, contributing to improving high-temperature strength. To obtain this effect, the Al content is set to 0.001% or more. However, excessive content of Al leads to a decrease in toughness. Therefore, the Al content is set to 0.600% or less. The Al content is preferably 0.002% or more, and more preferably 0.003% or more. Moreover, the Al content is preferably 0.550% or less, and more preferably 0.500% or less.
[0060] N: 0.001 to 0.150% N stabilizes the austenite phase and contributes to improving high-temperature strength. To obtain this effect, the N content is set to 0.001% or more. However, excessive content of N leads to a decrease in ductility. Therefore, the N content is set to 0.150% or less. The N content is preferably 0.002% or more, and more preferably 0.003% or more. Moreover, the N content is preferably 0.130% or less, and more preferably 0.100% or less.
[0061] O: 0.030% or less Excessive O content leads to deterioration of workability and ductility. For this reason, the O content is set to 0.030% or less. The O content is preferably set to 0.025% or less, and more preferably set to 0.020% or less. There is no need to set a lower limit for the O content, and it may be 0 (zero), but extreme reduction leads to an increase in steelmaking costs. For this reason, the O content is preferably set to 0.001% or more, and more preferably set to 0.003% or more.
[0062] The chemical composition of the second pipe is made up of the balance Fe and impurities. Note that "impurities" refer to substances that are mixed in due to various factors during the manufacturing process, including raw materials such as ores and scraps, when steel materials are industrially manufactured.
[0063] The chemical composition of the second tube may contain one or more elements selected from the group below in place of a portion of Fe. The reasons for this will be described below.
[0064] Total of Cu and / or Co: 6.00% or less Total of Mo and / or W: 8.00% or less The total of one or more selected from V, Nb, Ti and Ta: 2.00% or less B: 0.0200% or less Total of Ca and / or Mg: 0.0100% or less REM: 0.0500% or less
[0065] Total of Cu and / or Co: 6.00% or less Both Cu and Co are effective in increasing the stability of the austenitic structure and improving high-temperature strength, so they may be contained as necessary. However, both are expensive elements, and excessive inclusion of these elements leads to a decrease in ductility, so when these elements are contained, the total content of Cu and / or Co is set to 6.00% or less. The above total content is preferably 5.50% or less, and more preferably 5.00% or less. In order to reliably obtain the above effects, the above total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0066] Total of Mo and / or W: 8.00% or less Both Mo and W are dissolved in the matrix and contribute to improving high-temperature strength, so they may be contained as necessary. However, excessive content impairs the stability of the austenite structure and generates coarse intermetallic compounds and / or carbides during use at high temperatures, resulting in a decrease in toughness. Therefore, when contained, the total content of Mo and / or W is set to 8.00% or less. The above total content is preferably 7.50% or less, and more preferably 7.00% or less. In order to reliably obtain the above effects, the above total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0067] The total of one or more selected from V, Nb, Ti and Ta: 2.00% or less V, Nb, Ti and Ta may be contained as necessary because they all form fine carbonitrides during use at high temperatures and contribute to improving high-temperature strength. However, excessive content of these elements generates a large amount of coarse carbonitrides, which leads to a decrease in toughness, so when these elements are contained, the total content of one or more selected from these elements is set to 2.00% or less. The total content is preferably 1.90% or less, and more preferably 1.80% or less. If it is desired to reliably obtain the above effects, the total content is preferably 0.01% or more, and more preferably 0.02% or more.
[0068] B: 0.0200% or less B may be contained as necessary because it dissolves in carbides during high-temperature use, disperses finely, and contributes to improving high-temperature strength. However, if contained in excess, it is mixed into the weld metal during welding and increases solidification cracking susceptibility, so if contained, the B content is 0.0200% or less. The B content is preferably 0.0180% or less, and more preferably 0.0150% or less. If it is desired to reliably obtain the above effects, the B content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0069] Total of Ca and / or Mg: 0.0100% or less Both Ca and Mg may be added as necessary to improve hot workability. However, excessive addition significantly reduces cleanliness and impairs hot workability, so when added, the total content of Ca and / or Mg is set to 0.0100% or less. The total content is preferably 0.0080% or less, and more preferably 0.0060% or less. In order to reliably obtain the above effects, the total content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0070] REM: 0.0500% or less Like Ca and Mg, REM may be added as necessary to improve hot workability. However, excessive addition significantly reduces cleanliness and impairs hot workability, so if added, the REM content is set to 0.0500% or less. The REM content is preferably 0.0400% or less, and more preferably 0.0300% or less. If it is desired to reliably obtain the above effects, the REM content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0071] "REM" is a general term for 17 elements, including Sc, Y, and lanthanides, and the REM content refers to the total content of one or more REM elements. REM is generally contained in misch metal. For this reason, for example, misch metal may be added to the alloy to make the REM content fall within the above range.
[0072] (D) Average chemical composition of tubes 1 and 2 The first and second tubes according to the present invention must have the above-mentioned chemical compositions, and in addition, their average chemical compositions must satisfy a certain relational expression, for the following reasons.
[0073] When the double-walled pipe according to the present invention is welded using a welding material made of austenitic stainless steel or Ni alloy, the double-walled pipe (base material) melts, and the Si, P, S, and Sn contained therein are mixed into the weld metal. All of these elements lower the solidus temperature and increase the solidification cracking susceptibility of the weld metal. In particular, in the weld metal close to the fusion boundary, mixing during welding is insufficient, and the chemical composition of the weld metal is dominated by the influence of the base material.
[0074] In addition, since the weld metal near the boundary between the inner and outer pipes has an austenite single-phase solidification structure, it is susceptible to solidification cracking due to the influence of these elements. In order to stably prevent solidification cracking from occurring in this region, it is necessary to control the average values of Si, P, S, and Sn contents of the first and second pipes within a specified range based on a relationship that takes into account the degree of influence of each element.
[0075] Specifically, it is necessary to satisfy the following formula (i): The value on the left side of the following formula (i) is preferably 1.0500 or less, and more preferably 1.0000 or less. S ave +6×P ave +20×S ave +2×Sn ave ≦1.1000 (i) In the above formula, the meanings of each symbol are as follows: S ave : Average value of Si content of the first and second tubes (mass%) P ave : Average value of P content in the first and second pipes (mass%) S ave : Average value of S content in the first and second pipes (mass%) Sn ave : Average value of Sn content of the first and second tubes (mass%)
[0076] As mentioned above, the double-walled pipe (base material) melts during welding, and the S and Sn contained therein are mixed into the weld metal. These elements increase susceptibility to weld cracking, but if they are reduced too much, the penetration depth during welding decreases, making it easier for insufficient penetration to occur. In order to stably prevent insufficient penetration, it is necessary to control the average amount of S and Sn contained in the first and second pipes within a specified range based on a relationship equation that takes into account the degree of influence of each element.
[0077] Specifically, it is necessary to satisfy the following formula (ii): The value on the right side of the following formula (ii) is preferably 0.0020 or more, and more preferably 0.0025 or more. 0.0015≦4×S ave +Sn ave (ii) In the above formula, the meanings of each symbol are as follows: S ave : Average value of S content in the first and second pipes (mass%) Sn ave : Average value of Sn content of the first and second tubes (mass%)
[0078] (E) Welded joints The welded joint according to the present invention includes the above-mentioned double pipe. That is, it is a welded joint formed by joining a plurality of double pipes together. When assembling the double pipes by butt welding, an appropriate welding material may be selected according to the intended use.
[0079] For example, when welding a double-walled pipe in which the outer pipe is the first pipe (low alloy steel) and the inner pipe is the second pipe (high alloy steel), as is commonly done, the high alloy steel part is welded using austenitic stainless steel or Ni-based alloy welding material, and then the area near the boundary is welded using pure Ni welding material, and the remaining low alloy steel part is welded using carbon steel welding material, and a weld joint with the required performance can be obtained. Also, if the materials constituting the outer pipe and the inner pipe are reversed, the welding can be performed using the reverse method.
[0080] Furthermore, in the double-walled pipe according to this embodiment, a welded joint having the required performance can be obtained even if only a welding material for austenitic stainless steel or Ni-based alloy that solidifies as austenitic is used, without using multiple types of welding materials as described above. Therefore, the welded joint according to one embodiment of the present invention is preferably welded with a welding material for either austenitic stainless steel or Ni-based alloy. In this case, the welding material used and the weld metal formed preferably have the following chemical composition.
[0081] That is, the chemical composition of the welding material and the weld metal is, in mass%, C: 0.003 to 0.100%, Si: 0.01 to 1.50%, Mn: 0.01-2.50%, P:0.0400% or less, S: 0.0100% or less, Sn: 0.0300% or less, Sum of Cu and / or Co: 0~15.00%, Ni: 12.0-75.0%, Cr: 18.0%~27.0%, Sum of Mo and / or W: 0~10.00%, One or more selected from V, Nb, Ti, and Ta: 0 to 4.00% in total; B: 0~0.0200%, Total of Ca and / or Mg: 0~0.0100%, Al: 0.001 to 1.500%, N: 0.001 to 0.150%, O: 0.030% or less, The balance is Fe and impurities. It is preferable that the following formulae (iii) and (iv) are satisfied. S w +6×P w +20×S w +2×Sn w ≦1.1000% (iii) 0.0015%≦4×S w +Snw (iv) In the above formula, the meanings of each symbol are as follows: S w : Si content of welding material or weld metal (mass%) P w : P content of welding material or weld metal (mass%) S w : S content of welding material or weld metal (mass%) Sn w : Sn content of welding material or weld metal (mass%)
[0082] (F) Manufacturing method There are no particular limitations on the method for manufacturing a double-walled pipe, but for example, a material can be assembled by inserting a solid billet of high-alloy steel or low-alloy steel constituting the inner pipe into a hollow billet of low-alloy steel or high-alloy steel constituting the outer pipe, and then subjecting the assembled material to so-called "hot pipe making" such as hot extrusion and rolling to integrate the outer and inner pipes. This produces a double-walled pipe in which the outer pipe is the first pipe and the inner pipe is the second pipe, or a double-walled pipe in which the outer pipe is the second pipe and the inner pipe is the first pipe.
[0083] In addition, the billets are usually assembled in a vacuum or in an inert gas atmosphere to ensure the cleanliness of the mating surfaces. The hot-formed double-walled pipe may then be subjected to cold working such as rolling or drawing, and may then be subjected to heat treatment to form a double-walled pipe of a desired shape.
[0084] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples. EXAMPLES
[0085] Low alloy steels L1 to L7 and high alloy steels H1 to H7 having the chemical compositions shown in Table 1 were combined, and a double-walled pipe having a first pipe made of low alloy steel and a second pipe made of high alloy steel, a thickness of 6.5 mm, and an outer diameter of 63 mm was produced by hot-working, and used as a test pipe. When the outer pipe was the first pipe and the inner pipe was the second pipe, the thickness of the outer pipe was 4.2 mm and the thickness of the inner pipe was 2.3 mm, i.e., the ratio of the second pipe to the total pipe thickness was 0.35. On the other hand, when the outer pipe was the second pipe and the inner pipe was the first pipe, the thickness of the outer pipe was 1.6 mm and the thickness of the inner pipe was 4.9 mm, i.e., the ratio of the second pipe to the total pipe thickness was 0.25.
[0086] [Table 1]
[0087] After cutting a 100 mm long test piece from the test pipe, a groove was machined on one end of the test piece as shown in Figure 1. The grooves were butted together, and a solid bar with an outer diameter of 48 mm and a length of 250 mm, machined from a commercially available steel plate equivalent to SM400B as specified in JIS G 3106 (2008), was inserted into the steel pipe. Both ends were then welded to AWS A5.11-2005 ENiCrMo-3 using a covered metal arc welding electrode as specified, to create two restraint welded specimens for each test number, as shown in Figure 2.
[0088] In the groove of the restraint welded specimen, AWS A.5.14-2009 ERNiFeCr-1 with the chemical composition shown in Table 2 was used with the specified filler wire, and multi-layer welding was performed by TIG welding with a heat input of 8 to 12 J / cm.
[0089] [Table 2]
[0090] Four test pieces were cut out from each of the restraint-welded test pieces after multi-layer welding so that the cross section of the welded joint was the observation surface, and the test pieces were mirror-polished.
[0091] After that, the test pieces were corroded, and the presence or absence of defects was examined using an optical microscope for a total of eight cross sections (two test pieces x four cross sections) of the welded parts for each test number. Test pieces in which neither solidification cracking nor poor penetration was observed in any cross section were judged to have passed the test with an "A," test pieces in which neither solidification cracking nor poor penetration was observed in only one cross section were judged to have passed the test with an "B," and test pieces in which neither solidification cracking nor poor penetration was observed in two or more cross sections were judged to have failed the test with an "F."
[0092] The evaluation results are shown in Table 3.
[0093] [Table 3]
[0094] As can be seen from Table 3, the double-walled pipes that satisfy all the requirements of the present invention had no defects such as solidification cracks or poor penetration in the weld metal, and a sound weld joint was obtained. It has been confirmed that the chemical composition of the weld metal obtained satisfies the preferred chemical composition described above.
[0095] In contrast, in test numbers T2-2, T3-2, T3-9, T5-2 and T5-5, formula (i) was not satisfied, and solidification cracks occurred in the weld metal near the fusion line near the boundary between the inner and outer pipes. In test numbers T3-3, T3-10, T5-3 and T5-6, formula (ii) was not satisfied, and therefore the groove face was not melted sufficiently, which is called poor penetration.
[0096] The chemical compositions of the weld metal of these weld joints that do not satisfy the present invention satisfied the above-mentioned preferred chemical composition range on average, but it was determined that solidification cracking or poor penetration occurred in localized regions of the weld metal near the fusion boundary at the interface between the outer pipe and the inner pipe because they did not satisfy formula (i) or formula (ii).
[0097] As is clear from the above, it is understood that a sound welded joint can be obtained only when a double pipe that satisfies all of the requirements of the present invention is used. [Industrial Applicability]
[0098] According to the present invention, it is possible to obtain a double-walled pipe which is capable of preventing cracks from occurring in the weld metal during butt welding of the pipes and which can stably obtain a sound welded joint.
Claims
1. A double pipe including a first pipe and a second pipe, The double pipe has a structure in which an outer pipe and an inner pipe are metallurgically bonded to each other, the outer tube is the first tube and the inner tube is the second tube, or the outer tube is the second tube and the inner tube is the first tube; The chemical composition of the first tube is, in mass%, C: more than 0.060% and not more than 0.400%; Si: 0.01-1.00%, Mn: 0.01 to 1.20%, P: 0.0350% or less, S: 0.0150% or less, Sn: 0.0005-0.0400%, Al: 0.040% or less, N: 0.050% or less, O: 0.030% or less, The balance is Fe and impurities. The chemical composition of the second tube is, in mass%, C: 0.003-0.100%, Si: 0.01-1.50%, Mn: 0.01 to 2.20%, P: 0.0400% or less, S: 0.0100% or less, Sn: 0.0005-0.0300%, Ni: 7.0 to 52.0%, Cr: 15.0-27.0%, Al: 0.001-0.600%, N: 0.001-0.150%, O: 0.030% or less, The balance is Fe and impurities. The following formulas (i) and (ii) are satisfied: double tube. Yes ave +6×P ave +20×S ave +2×Sn ave ≦1.1000 ・・・(i) 0.0015≦4×S ave +Sn ave ・・・(ii) In the above formula, the meanings of each symbol are as follows: S ave Average value of Si content of the first and second tubes (mass%) P ave : Average value of P content in the first and second pipes (mass%) S ave : Average value of S content in the first and second pipes (mass%) Sn ave : Average value of Sn content of the first and second tubes (mass%)
2. The chemical composition of the first tube is, in mass%, replacing a part of Fe, Cr: 9.50% or less, The total content of one or more selected from Cu, Ni and Co: 1.00% or less, Sum of Mo and / or W: 4.00% or less, The total of one or more selected from V, Nb, Ti, and Ta: 1.00% or less, B: 0.0200% or less, The sum of Ca and / or Mg: 0.0100% or less, REM: 0.0500% or less, Contains one or more selected from the group consisting of The double pipe according to claim 1.
3. The chemical composition of the second tube is, in mass%, replacing a part of Fe, Total of Cu and / or Co: 6.00% or less, Sum of Mo and / or W: 8.00% or less, The total of one or more selected from V, Nb, Ti and Ta: 2.00% or less, B: 0.0200% or less, The sum of Ca and / or Mg: 0.0100% or less, REM: 0.0500% or less, Contains one or more selected from The double pipe according to claim 1 or 2.
4. A welded joint comprising the double pipe according to any one of claims 1 to 3.
Citation Information
Patent Citations
Corrosion-resisting duplex tube
JP1989139740A
Manufacture of two-layer pipe joint
JP1989180720A
Alloy having corrosion resistance in combustion environment in which v, na, s and cl are present and multi-ply steel tube
JP1992221034A
Alloy for waste incineration furnace boiler and multiple layered steel tube
JP1992329852A
Alloy having corrosion resistance in combustion environment in which v, na, s and cl are present and multiple layered steel tube
JP1993017841A
